Potential of Silver Craft Product through to Community-Based for Tourism Sustainability in Celuk Village - Wisudawati, Ni Nyoman Sri; Maheswari, A.A Istri Ari (International Research Journal of Management, IT & Social Sciences, 2018)
Celuk village has been known as a center of silver industry. In its current development of tourism, the purchasing power of tourists has decreased. The development of tourism trends with the changing mindset to do traveling was given some impact on it. Tourist reduced interest in buying silver, so the economy of Celuk villagers was weakening. Tourist more interested in interacting and directly involved tourism activities in an area where they visited especially in terms of unique social and cultural. From the research results obtained the tourism potential that can be developed in the Celuk village as a center of silver industry quite a lot and there also can develop supporting facilities for tourism activities as a tourist attraction. The potential of tourism products can be developed in Celuk village such as special interest tourism through  to  silver craft class by handmade process, educational tourism with a tour around the process how to make silver craft by hand (traditional) or by modern machine (silver process print), visiting the gallery/art shop to see the results of silver handicrafts and in  the same time can bought directly, Celuk Jewelry Festival held every year on a particular month, accommodation (homestay) at craftsmen house with simple concept according to the daily silver craftsman lifeâs especially for tourists who want to learn to make silver crafts more than a day.